PENGARUH METODE BERCERITA BERMEDIA VISUAL TERHADAP KEMANDIRIAN ANAK KELOMPOK B TK AMALYA BINTAN RIAU - Lina Eka Retnaningsih; Sri Zulfida; Nadya Nela Rosa; Sayyidah Azimah (JCE (Journal of Childhood Education), 2021)
This study is fostered by the low independence of Amalya Kindergarten's group B children in learning activities. Most of the children were not able to do the assigned tasks independently at school, not able to put items/ objects to their original places independently, feared to appear alone in front of the class, and tended to ask teachers’ helps when doing various activities at school. Therefore, it was necessary to use an appropriate and fun method for children, namely by using visual media storytelling methods to increase their independence. The objective of the study was to find out the independence of the children of Amalya Kindergarten Group B after using the visual media storytelling method. A pre-experimental research design with a one-group pretest-posttest design was carried out in this study. The data were collected by using observation, documentation and interview. The subjects of this study were 10 children. The data obtained in the field were analyzed by using the Wilcoxon’s match pairs test data analysis technique, with the formula Tobtained<Ttable. If Tobtained<Ttable, then this study has a significant influence between the 2 variables. From the results, it was found that the total score of the independent pretest of group B children was 59 with an average score 5.9 each subject and the results of the total posttest score was 120 with an average score 12 each subject. The results of the Wilcoxon’s match pairs test show that Tobtained = 0 is smaller than Ttable with a significant level of 5% = 8, so Tobtained<Ttable (0<8). Thus, it can be concluded that Ha is accepted and Ho is rejected. This means that the research hypothesis stating that there is an influence of using visual media storytelling methods on the independence of Amalya Kindergarten's group B children, Bintan Regency, Riau Islands, is accepted.